SURVEI PENGGUNAAN MEDIA PEMBELAJARAN LADDER DRILL DALAM PEMBELAJARAN LARI JARAK PENDEK - Azis, Abdul; Kurniawan, Febi; Gustiawati, Resty (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2020)
The purpose of making this skripsi is to find out, analyze, and identify the use of ladder drill learning media in short distance learning in vocational students in North Cikarang District, Bekasi Regency. This research is quantitative descriptive. The method used is a survey method. Data collection techniques in the form of a questionnaire. Data was collected at schools in North Cikarang sub-district. The subjects used in this study were all physical education teachers in North Cikarang sub-district, totaling 18 teachers. Based on the results of research on vocational schools in North Cikarang District 94% of teachers already knew the ladder drill learning media and already knew its shape, 67% of the teachers already had ladder drill learning media at their school, 94% of teachers already knew how to use ladder drill learning media, 56% teachers use ladder drill media in Physical Education learning, 67% of teachers use ladder drill learning media to train speed and agility, 50% of teachers use ladder drill learning media to train foot coordination, 94% of teachers state that ladder learning media are useful for learning Physical education, 67% of teachers state that the ladder drill learning media can increase the speed of running short distances, 94% of teachers already know that there is scope in physical education. Thus it can be stated that the ladder drill learning media is related to help increase the speed of running short distances, because more than half of the physical education teachers in vocational high schools in North Cikarang have used the ladder drill learning media.